Finance for Integrated Landscape Management: Processes that support integrated landscape initiatives and make access to finance more inclusive - Primo L.; Louman, Bastian; Stoian, D.; Pamerneckyte, G. (Tropenbos International and World Agroforestry Center, 2021)
This methodology helps identify the key stakeholders linked to financial flows for integrated landscape management, their perspectives and motivations, and the mechanisms used to channel funding from investors through brokers or intermediaries to individual or recipient groups that support integrated landscape initiatives.